Organic Semiconducting Agents for Deep‐Tissue Molecular Imaging: Second Near‐Infrared Fluorescence, Self‐Luminescence, and Photoacoustics - Miao, Qingqing; Pu, Kanyi (Advanced materials (Weinheim), 2018)
Optical imaging has played a pivotal role in biology and medicine, but it faces challenges of relatively low tissue penetration and poor signal‐to‐background ratio due to light scattering and tissue autofluorescence. To overcome these issues, second near‐infrared fluorescence, self‐luminescence, and photoacoustic imaging have recently emerged, which utilize an optical region with reduced light–tissue interactions, eliminate real‐time light excitation, and detect acoustic signals with negligible attenuation, respectively. Because there are only a few endogenous molecules absorbing or emitting above the visible region, development of contrast agents is essential for those deep‐tissue optical imaging modalities. Organic semiconducting agents with π‐conjugated frameworks can be synthesized to meet different optical imaging requirements due to their easy chemical modification and legible structure–property relation. Herein, the deep‐tissue optical imaging applications of organic semiconducting agents including small‐molecule agents and nanoparticle derivatives are summarized. In particular, the molecular engineering and nanoformulation approaches to further improve the tissue penetration and detection sensitivity of these optical imaging modalities are highlighted. Finally, current challenges and potential opportunities in this emerging subfield of biomedical imaging are discussed. Molecular optical imaging, including second near‐infrared fluorescence, self‐luminescence, and photoacoustic imaging, provides enhanced tissue penetration depth and detection sensitivity as compared with traditional optical imaging. The recent development of organic semiconducting agents for these deep‐tissue optical imaging modalities are summarized and the molecular design guidelines to amplify the signal intensity, improve the sensing specificity, and enhance the tissue penetration are highlighted.